Student Behavior Towards the Video Reels Algorithm for Psychosocial Development-Based Counseling - Nakhma'ussolikhah; Mohammad Iqbal Al-Ghazali (Ilmu Inovasi Nusantara, 2026)
Individual development is fundamentally rooted in self-awareness and the ability to understand oneself, yet many university students experience difficulties in recognizing personal problems and making independent decisions. This condition indicates a gap in counseling approaches that are responsive to students’ psychosocial development and digital lifestyles. Therefore, innovative counseling strategies that integrate psychosocial perspectives and digital media are needed to enhance students’ comprehensive self-understanding. This study aims to enhance students’ self-understanding through counseling services based on psychosocial development, utilizing real-life videos as a medium for counseling. The focus is on exploring how digital content aligned with students’ lived experiences can support the identification of problems, reflection, and decision-making processes. The research employed a qualitative methodology using a phenomenological approach grounded in social media experiences. The participants consisted of 15 students from the Guidance and Counseling Islamic Education (BKPI) program. From this group, three students were purposively selected based on identified problem indicators. Data were collected through systematic observation and in-depth interviews to capture students’ experiences, perceptions, and meaning-making processes related to the use of reel-life videos in counseling sessions. The findings reveal that reel-life videos effectively assist counselors in identifying students’ personal problems. The relevance of the video content, supported by social media algorithms, enables students to relate their experiences to the issues presented. Furthermore, students demonstrate increased independence in making decisions and formulating solutions to their problems. The alignment between the problems encountered and the solutions presented in the videos facilitates deeper self-reflection and problem-solving. This study suggests that reel-life videos can serve as an innovative counseling strategy that aligns psychosocial development with digital media, providing practical insights for counselors in designing adaptive, student-centered counseling services in the digital era